DAMPAK BANTUAN MILITER TERHADAP DINAMIKA POLITIK INTERNASIONAL - Aris Sarjito (Sawala : Jurnal Administrasi Negara, 2024)
Abstract This research explores the intricate interplay between military assistance and international political dynamics, focusing on its implications for regional power structures. Grounded in Power Transition Theory, the study aims to unravel the complex web of relationships influenced by military aid, examining its intended and unintended consequences. Leveraging qualitative research methods through the analysis of secondary data, three key dimensions are investigated: Military Assistance and Power Transition Theory, Unveiling Diplomatic Dynamics: Military Assistance, Bilateral Relations, and Alliance Politics, and Unintended Consequences: Military Assistance, Security Dynamics, and the Specter of Arms Races. The findings highlight the multifaceted impact of military assistance on regional power dynamics, shedding light on its role in shaping diplomatic relations, influencing alliance politics, and potentially triggering unintended security consequences such as the specter of arms races. This research contributes to a deeper understanding of how military aid shapes the global geopolitical landscape. In conclusion, it emphasizes the need for nuanced policy considerations to mitigate unintended outcomes while harnessing the potential positive impacts of military assistance. Keywords: alliance politics, bilateral relations, diplomatic dynamics, military assistance, power transition